Fiduciary Blind Spot: The Failure of Institutional Investors to Prevent the Illegitimate Use of Working Americans’ Savings for Corporate Political Spending - Leo E. Strine Jr. (Washington University Law Review, 2020)
For decades, American workers have been subjected to increasing pressure to become forced capitalists, in the sense that to provide for retirement for themselves, and to pay for college for their children, they must turn part of their income every month over to mutual funds who participate in 401(k) and 529 programs. These “Worker Investors” save for the long term, often hold portfolios that are a proxy for the entire economy, and depend on the economy’s ability to generate good jobs and sustainable growth in order for them to be able to have economic security. In recent years, there has been a heartening improvement in the self-awareness of the major mutual fund families—BlackRock, Vanguard, State Street, and Fidelity (the “Big Four”)—that have Worker Investors’ capital. This Big Four has grown enormously because of the legal pressures that generate capital inflows to them every month from Worker Investors. To their credit, the Big Four recognize that they have a duty to think and act in a way aligned with the interests of Worker Investors by encouraging the public companies in which they invest to implement business plans that will generate sound long-term growth. In fact, the Big Four have recently recognized that unless public companies act in a manner that is environmentally, ethically, and legally responsible, they are unlikely to be successful in the long run. Thus, the Big Four are more willing than ever to second-guess company management to fulfill their fiduciary duties. In one area, however, the Big Four continue to have a fiduciary blind spot: they let corporate management spend the Worker Investors’ entrusted capital for political purposes without constraint. The Big Four abdicate in the area of political spending because they know that they do not have Worker Investors’ capital for political reasons and because the funds do not have legitimacy to speak for them politically. But mutual funds do not invest in public companies for political reasons, and public company management has no legitimacy to use corporate funds for political expression either. Thus, a “double legitimacy” problem infects corporate political spending. This Article identifies and illustrates this double legitimacy problem, and shows why unconstrained corporate political spending is contrary to the interests of Worker Investors. Precisely because Worker Investors hold investments for the long term and have diversified portfolios that track the whole economy, political spending by corporate managers to tilt the regulatory playing field is harmful to them. Worker Investors are human beings who suffer as workers, consumers, and citizens when companies tilt the regulatory process in a way that allows for more pollution, more dangerous workplaces, less leverage for workers to get decent pay and benefits, and more unsafe products and deceptive services. But even as diversified investors, unconstrained corporate political spending is likely to create harm, as both common sense and empirical evidence suggest. Not only that, there is no danger that public companies would have too little voice in the political process if their spending were subject to constraint by stockholders. Corporations have many other tools, including their own Political Action Committees (“PACs”) funded by voluntary contributions, their lobbying expenditures, and the influence they wield as employers and taxpayers—tools that made business interests predominate in political spending even before Citizens United let them free to spend treasury funds without inhibition. For these reasons, the case against unconstrained corporate political spending is very strong. As of now, however, the Big Four refuse to even support proposals to require the very disclosure they would need if they were to monitor corporate political spending. And their capacity to monitor if they have the information is lacking. But, if the Big Four open their fiduciary eyes and follow the recommendation of the late industry icon Jack Bogle, and vote to require that any political spending from corporate treasury funds be subject to approval of a supermajority of stockholders, they alone could cure the double legitimacy problem of corporate political spending. Because of their substantial voting power, the support of the Big Four would ensure that this check on illegitimate corporate political spending would be put in place and thus make an important contribution to restoring some basic fairness to our political process.
Keywords: Fiduciary duty; Political speech; Political spending; Corporations; Investors; Corporate governance; Mutual funds; Fiduciary